Comparison of Two US Sheep Scrapie Isolates Supports Identification as Separate Strains. (November 2016) - Moore, S. J.; Smith, J. D.; Greenlee, M. H. West; Nicholson, E. M.; Richt, J. A.; Greenlee, J. J.
Scrapie is a naturally occurring transmissible spongiform encephalopathy of sheep and goats. There are different strains of sheep scrapie that are associated with unique molecular, transmission, and phenotype characteristics. However, in the United States, very little is known about the potential presence of scrapie strains. Scrapie strain and PRNP genotype could both affect susceptibility, potential for transmission, incubation period (IP), and control measures required for eliminating scrapie from a flock. The investigators evaluated 2 US scrapie isolates, No. 13-7 and x124, after intranasal inoculation to compare clinical signs, IPs, spongiform lesions, and patterns of PrP Sc deposition in sheep with scrapie-susceptible PRNP genotypes (QQ171). After inoculation with x124, susceptibility and IP were associated with valine at codon 136 (V136) of the prion protein: VV136 sheep had short IPs (6.9 months), those in AV136 sheep were 11.9 months, and AA136 sheep did not develop scrapie. All No. 13-7 inoculated sheep developed scrapie, with IPs of 20.1 months for AA136 sheep, 22.8 months for AV136 sheep, and 26.7 months for VV136 sheep. Patterns of immunoreactivity in the brain were influenced by inoculum isolate and host genotype. Differences in PrP Sc profiles versus isolate were most striking when examining brains from sheep with the VV136 genotype. Inoculation into C57BL/6 mice resulted in markedly different attack rates (90.5% for x124 and 5.9% for No. 13-7). Taken together, these data demonstrate that No. 13-7 and x124 represent 2 distinct strains of scrapie with different IPs, genotype susceptibilities, and PrP Sc deposition profiles.